2016
DOI: 10.1039/c6py00908e
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the synthesis of bio-based aromatic polyesters: novel copolymers derived from vanillic acid and ε-caprolactone

Abstract: A new and sustainable pathway for the synthesis of polyesters and copolyesters derived from vanillic acid is reported. The one-pot procedure does not require either solvents or purification steps. New bio-based crystalline copolymers with tunable thermal properties are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 48 publications
6
59
1
Order By: Relevance
“…The glass‐transition temperature ( T g ) of a polymer depends on the rigidity or flexibility of its structure, and the value was obtained from the DSC cooling curve [Figure (b)]. It is governed by intermolecular forces of attraction, the presence of thermostable moieties and stiffening groups, and crosslink density . The T g of the thermoset in the absence of HBGP was found to be 37 °C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The glass‐transition temperature ( T g ) of a polymer depends on the rigidity or flexibility of its structure, and the value was obtained from the DSC cooling curve [Figure (b)]. It is governed by intermolecular forces of attraction, the presence of thermostable moieties and stiffening groups, and crosslink density . The T g of the thermoset in the absence of HBGP was found to be 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Further crosslinks between chains restrict the chain motion and thus increase T g . The presence of bulky pendant groups like benzene rings can also restrict the rotational freedom, leading to high T g , so with the increase in wt % of HBGP, the T g value increases. These values are higher than that of a citric acid–based waterborne polyester …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the thermal processes [glass transition ( T g ), melting ( T m ), and decomposition ( T d ) temperatures] decreased with increasing methoxy side chains ( p HB > VEB > SEB), and increasing alkyl chain length. It was previously shown that polyethylene vanillate (PEV) with a T g ≈ 71 °C and T m ≈ 239 °C displayed thermal properties closest to PET ( T g ≈ 67 °C and T m ≈ 265 °C) …”
Section: Introductionmentioning
confidence: 99%
“…In this series of polymers, Tg was ranging between 50 and 70 • C and Tm between 170 and 239 • C were reported. A more sustainable chemical pathway from vanillic acid to polyethylene vanillate has been recently reported [323]. In fact, etherification reactions of phenolic compounds with a bio-based reagent, ethylene carbonate, instead of chloroethanol, represent an eco-friendly way to improve the reactivity of the phenolic functionality.…”
Section: Valorization Of Ferulic Acid (Fa) and Aromatic Compounds As mentioning
confidence: 99%